DIGITALISASI UMKM DAN PERENCANAAN ANGGARAN SERTA DAMPAKNYA TERHADAP PENINGKATAN PENDAPATAN (STUDI PADA UMKM DI KEC. WENANG KOTA MANADO) - Meilany M. J Solung; Daisy S. M Engka; Jacline I. Sumual (PT. Hasba Edukasi Mandiri, 2025)
This research aims to analyze the influence of Micro, Small, and Medium Enterprises (MSME) digitalization and budget planning on increasing MSME income in Wenang District, Manado City. Data was collected through questionnaires from 30 MSME actors and analyzed using SEM-PLS. The analytical method employed was Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via the SmartPLS application. The results show that MSME digitalization does not have a significant effect on income, while budget planning has a positive and significant effect on increasing MSME income. These findings are expected to provide input for MSME actors to improve the effectiveness of digitalization and budget management, and to serve as a reference for the government in formulating technology-based MSME empowerment policies.